2000
DOI: 10.1038/sj.jea.7500112
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution, aeroallergens and cardiorespiratory emergency department visits in Saint John, Canada

Abstract: Existing studies of the association between air pollution, aeroallergens and emergency department ( ED ) visits have generally examined the effects of a few pollutants or aeroallergens on individual conditions such as asthma or chronic obstructive pulmonary disease. In this study, we considered a wide variety of respiratory and cardiac conditions and an extensive set of pollutants and aeroallergens, and utilized prospectively collected information on possible effect modifiers which would not normally be availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 42 publications
7
60
1
Order By: Relevance
“…For example, Stieb et al (2000) demonstrated significantly increased ED attendances for angina/myocardial infarction with SO 2 only and all cardiac ED attendances with O 3 only, whereas we demonstrated significant percentage increases in ED attendances in IHD for NO 2 and CO, and in cardiac disease for all pollutants (except O 3 ). Unfortunately, Stieb et al (2000) did not provide ICD codes for their categories of CVD and therefore we are unable to directly compare their results with ours. Our results are more consistent with those of Metzger et al (2004), who also found increased ED attendances for all CVD with PM 2.5 , NO 2 and CO, and for IHD with NO 2 .…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…For example, Stieb et al (2000) demonstrated significantly increased ED attendances for angina/myocardial infarction with SO 2 only and all cardiac ED attendances with O 3 only, whereas we demonstrated significant percentage increases in ED attendances in IHD for NO 2 and CO, and in cardiac disease for all pollutants (except O 3 ). Unfortunately, Stieb et al (2000) did not provide ICD codes for their categories of CVD and therefore we are unable to directly compare their results with ours. Our results are more consistent with those of Metzger et al (2004), who also found increased ED attendances for all CVD with PM 2.5 , NO 2 and CO, and for IHD with NO 2 .…”
Section: Discussioncontrasting
confidence: 47%
“…Metzger et al (2004) also reported that associations between air pollutants and CVD attendances tended to be highest in the colder months compared to the warmer months. In contrast, Stieb et al (2000) demonstrated that air pollutant effects on ED attendances for cardiac disease were generally greater in the summer months compared to all year effects except for PM 2.5 , where the effect was smaller in summer. We also found mainly negative associations between stroke ED attendances (fewer ED attendances) and air pollutants in the warm period compared to the cool period, and in some cases the negative associations were statistically significant.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our previous asthma panel studies did not find confounding of air pollutant associations by outdoor pollen or fungi (1,7,8). Several time-series investigations have found associations between asthma hospital admissions and both outdoor air pollutants (particles, NO 2 , or O 3 ) and pollen or fungi, but none has found any confounding between aeroallergens and these pollutants (54,60,61). In two studies, there was evidence that SO 2 , NO 2 , and O 3 enhanced the effect of grass pollen on asthma admissions (54,60), although there was a negative interaction between O 3 and tree pollen in one of these studies (54).…”
Section: Discussionmentioning
confidence: 99%
“…In 1998, the National Research Council 14 stressed the need for additional research to better understand the interactions between PM and gaseous co-pollutants in relation to human health. Since then, several epidemiological studies [15][16][17][18][19][20] have considered the combined effects of co-pollutants and PM on public health and have discovered significant associations between mortality or morbidity and variables such as CO, NO 2 , SO 2 , O 3 , temperature, and aeroallergens. In some instances, these associations were stronger than those between PM and the health endpoints being considered.…”
Section: Discussionmentioning
confidence: 99%